BIMBINGAN ROHANI SEBAGAI MEDIA PENDIDIKAN AKIDAH DAN AKHLAK TERHADAP PASIEN RAWAT INAP DI RUMAH SAKIT MUHAMADIYAH GRESIK - Nur fadlilah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2023)
The aim of the research is to find out spiritual guidance as a means of educating faith and morality in the healing process of patients, so that there are no deviations in their beliefs when they are tested sick, so that they do not end up in the endeavor to recover and then seek treatment by way of shirk. There are three formulations of the problem as the background to this goal, namely: One, spiritual guidance as a medium for educating the faith and morals of inpatients; Two, impacts of faith and morals education on inpatients; Three, obstacles were found during spiritual guidance at the Muhammadiyah hospital Gresik. The research type used in this research is qualitative research. The methods used in this research are observation, interviews, and documentation, namely: to inpatients, spiritual guidance officers, and hospital management. While the methods used in spiritual guidance are carried out in three ways, namely: audio, oral, and textbooks. The results obtained in spiritual guidance as a medium for educating the faith and morals of inpatients can increase the hope of recovery. Inpatients give a positive impression of the spiritual guidance program implemented at RSMG. The most effective method is done orally through advice. The most serious obstacle to spiritual guidance is the patient's rejection. In addition, there are obstacles to hospital management and to religious diversity in the spiritual guidance carried out at RSMG. There needs to be a comprehensive program system improvement to reduce the obstacles that have been obtained so far.